FEUDAL HERITAGE : SOURCE OF CORRUPTION, COLLUSION, AND NEPOTISM - Suhartono Suhartono (Humaniora, 1999)
The political development in Indonesia at the present time has been marked by a terminology of change, namely "reformation" which includes three main causes of the failure of the New Order led by President Soeharto . This phenomenon signifies that the New Order has been involved in practices of corruption, collusion, and nepotism (CCN). These practices have brought about instability in all sectors, and the most important is a sharp decrease in public welfare. During the New Order nobody would express their opinions frankly on Soeharto's involvement in CCN. He held the office of president for 32 years with an opresive bureaucracy that tended to perpetuate a system created by an absolute ruler . Student activists in several universities in Indonesia demanded reduction of soaring prices and asked Soeharto to step down . Their incessant demands for political economic reforms, were endorsed by university students of most universities in Indonesia . This was followed by mass demonstrations until the downfall of Soeharto in May 21, 1998 .